PERAN BRANDING TERHADAP KEPUTUSAN PEMBELIAN DIMEDIASI WORD OF MOUTH MARKETING DI PERUSAHAAN LULUR SEKAR JAGAT - Ni Luh Ketut Ayu Sudha Sucandrawati; I Dewa Nyoman Usadha (Universitas Mahendradatta, 2022)
This research is motivated by the rapid development of the businessworld which includes the emergence of similar competitors, therefore it is important to have a strategy in maintaining the company by using the right salespromotion. Branding is one of the promotions that is able to create a goodreputation in a brand and a good word of mouth (Word of Mouth Marketing)communication strategy is also able to influence purchasing power or purchasingdecisions by consumers. The aims of this investigation was to make sure the effectof Branding on the Purchasing Decision of Lulur Sekar Jagat and the Effect ofBranding on the Purchase Decision of Lulur Sekar Jagat mediated by Word ofMouth Marketing. This investigation is a quantitative study with a survey methodwhere the population are consumers who have purchased or used the product ofLulur Sekar Jagat and the sample used is 65 people determined by nonprobabilitysampling technique. Path analysis technique (path analysis) with thehelp of simple regression and Sobel test to answer the hypothesis in this studywith the results showing that (1) Branding has a positive and significant effect onpurchasing decisions for Lulur Sekar Jagat (2) Branding has a positive effect onpurchasing decisions for Lulur Sekar Jagat mediated by word of mouthmarketing. There are suggestions for companies that are expected to continue toinnovate and maintain product quality and continue to do branding on productsso that they can always attract consumers and companies should improvepromotional media in accordance with trends and the use of the latest technologyand not only rely on word of mouth promotion mediation to increase volume.company sales.